2005
DOI: 10.1161/01.res.0000166325.00383.ed
|View full text |Cite
|
Sign up to set email alerts
|

Role of Histamine Produced by Bone Marrow–Derived Vascular Cells in Pathogenesis of Atherosclerosis

Abstract: Abstract-To clarify the role of histamine-producing cells and its origin in atherosclerosis, we investigated histidine decarboxylase (HDC; histamine-producing enzyme) expression in murine arteries with vascular injuries after the animal had received transplanted bone marrow (BM) from green fluorescent protein (GFP)-transgenic mice. The neointima in the ligated carotid arteries contained BM-derived HDC ϩ cells that expressed macrophage (Mac-3) or smooth muscle cell antigen (␣-SMA). In contrast, the HDC ϩ BM-der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
128
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(138 citation statements)
references
References 36 publications
9
128
0
1
Order By: Relevance
“…One of these studies showed that the histamine H1 receptor antagonist reduced intimal hyperplasia (13); the other study reported that histamine synthesis enzyme knock-out mice (HDC Ϫ/Ϫ mice) showed reduced neointimal thickening and a decreased intima-to-media thickness ratio (14). In regard to how histamine influences inflammation and atherosclerosis in endothelial cells, evidence has shown that histamine induces expression of genes such as p-selectin (9), ICAM1, VCAM1 (10), IL6, IL8 (8), cyclooxygenase-2 (27), and tissue factor (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these studies showed that the histamine H1 receptor antagonist reduced intimal hyperplasia (13); the other study reported that histamine synthesis enzyme knock-out mice (HDC Ϫ/Ϫ mice) showed reduced neointimal thickening and a decreased intima-to-media thickness ratio (14). In regard to how histamine influences inflammation and atherosclerosis in endothelial cells, evidence has shown that histamine induces expression of genes such as p-selectin (9), ICAM1, VCAM1 (10), IL6, IL8 (8), cyclooxygenase-2 (27), and tissue factor (11).…”
Section: Discussionmentioning
confidence: 99%
“…Histamine also induces tissue factor expression in smooth muscle cells (11), and smooth muscle cell proliferation (12,13). Most importantly, the antagonists of histamine receptor 1 (H1) reduce thickened intimas in mice (13), and recently, HDC knock-out mice showed reduced neointimal thickening (14). All of this accumulating evidence supports the notion that histamine promotes the development and progression of atherosclerosis.…”
mentioning
confidence: 82%
“…A pathogenetic role of histamine in atherogenesis was highlighted by recent studies demonstrating that histidine decarboxylase as well as the H 1 -receptor are expressed in atherosclerotic human arteries [11], and that mice deficient in histidine decarboxylase exhibit reduced intimal thickening after vascular injury [10]. Invasion and activation of leukocytes are early events in atherogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Considering our finding that the SMCs in the advanced atherosclerotic lesions of hPRDX4 + / + /apoE -/ -mice showed very low proliferative activity based on MIB-1 staining, the activated PDGF expression and secretion would enhance SMC migration, particularly in the thickened fibrous caps of atheromatous plaques, and may therefore reduce plaque vulnerability in hPRDX4 + / + / apoE -/ -mice. Accordingly, overexpression of hPRDX4 might be closely related to PDGF-induced migratory signaling in neointimal SMCs, the possible origins of which could include PRDX4-expressed medial SMCs, circulating SMC precursor cells, or adventitial SMC progenitor cells (19,20,32).…”
Section: Role Of Prdx4 In Atherosclerosismentioning
confidence: 99%